Modeling & Control of Methoxy-Methyl-Heptane Separation Process - Ahmad Anas B Awang, Ahmad Anas (Universiti Teknologi Petronas, 2011)
A study in Lehigh University Bethlehem, Pennsylvania has proposed the chemical 2-methoxy-2-methylheptane (MMH) as a great alternative gasoline additive to replace methyl tert-butyl ether (MTBE) in order to avoid groundwater contamination. In MMH production process, the chemistry involves the liquid phase reversible reaction of methanol with 2-methyl-1-heptene (MH) to form MMH. However, methanol and MH also undergo an undesirable reaction to form dimethyl ether (DME) and 2-methyl-2-heptanol (MHOH). The approach adopted in this paper is to do a modeling and control of the MMH separation process to achieve a specified yield of MMH. The MMH separation process features three distillation columns in series. The first distillation column separate DME from the rest of product, second distillation column separates MH from the rest of product, and the third distillation column separates the final product MMH from MHOH. Process model is obtained through system identification using input-output testing data. A model predictive control strategy would be developed to replace regulatory control in order to sustain production at optimum cost the current regulatory control. This project also explained the function of gasoline additive, why replacement of MTBE with MMH as gasoline additive is needed, and MTBE’s effect on environment.